Developing the Framework Using Deep Neural Network for Detection of Spam and Fake Spam Messages in Twitter - N. Anil Kumar,; Thatha Anusha,; Nagamalla Durga Prasad,; Maddala Bala Manikanta,; Boddu Swathi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Social media plays vital role among the user communities for social gathering, entertainment, communication, sharing knowledge so on. Twitter is one such network to connect millions of users to share information. Nowadays, there are humpteen numbers of users using social media for social engagements. Due to the fact that wide publicity of individuals and products get viral in social media, everyone wish to use social media as a platform to promote their product. Furthermore, large number of people relies on social media contents to take decisions. Twitter is one of the social media platforms to post the media contents by the user. Spammers are illegal users intrude the twitter account and send the duplicate messages to promote advertisement, phishing, scam and personal blogs etc. In this paper, a novel spam detection mechanism is introduced to detect the suspicious users on twitter. The system has been designed such a way that it initially set with semi-supervised at the tweet level and update into supervised level for learning the input tweets to detect the spammers. The proposed system will also identify the type of spammers and will also remove duplicate tweets. We have applied with multi-classifier algorithms like naïve Bayesian, K-Nearest neighbor and Random forest into twitter data set and the performance is compared. The experimental result shows very promising results.
Keywords: Twitter Spam; Multi-classifier; Classification; Bayesian; K-Nearest neighbor; Random forest